Pengembangan Aplikasi Sistem Pelayanan Masyarakat Berbasis Android (Studi Kasus : Kecamatan Payaraman Ogan Ilir) - Wirah Rahmatullah; Afriyudi Afriyudi (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
In public administration services almost every day requests for incoming letters, both requests for business place permits, SK Domicile and other documents. The data collection of letters requested by residents of Payaraman District will be handled directly through the admin where the data will be entered into the request list using a computer, then the letter will be printed for signature, residents have to wait for the letter with uncertain terms. This problem was raised due to the large number of public complaints in issuing a decree that had been signed by the sub-district head. This research uses extreme programming method in development by using CI framework for admin and flutter framework for users. The results of the study are that residents of Payaraman District can access the application to request a letter request which will contain identities such as ID cards and permits or decrees that will be sent back via the web admin to the application according to the request of residents who access/request a letter.